Patients presenting to the emergency department due to alcohol consumption and its surgical dimension - Gül, Aysel; Aygin, Dilek (Journal of Dependence, 2021)
Today, alcohol which is one of most commonly used substance on global level constitutes the etiology of many diseases. Data on alcohol consumption foreshadow the possible rapid increase in its consumption in the coming years. A significant part of the admissions to hospitals, and the clinical prognosis of patients who have undergone diagnostic or surgical processes consist of the problems aroused by alcohol consumption. The patient load created by this active substance especially in emergency services, perioperative process management and the healthcare services is an important problem. Because of that alcohol presents a toxic property, it is needed special approaches and practices in diagnosis, treatment and examination processes of individuals who are detected as drunk in the admissions to healthcare institutions. This compilation is written for the purpose of analyzing the literature data towards the effects of alcohol/alcohol consumption on human organism, and the points to take into consideration about the individuals’ admissions to emergency service and their perioperative processes.
Keywords: Alcohol drinking; emergency; surgery